ECONOMIC VALUATION OF THE Eucalyptus urograndis PRODUCTION IN TWO TYPES OF CONTAINERS - de Oliveira, Dariane Priscila Franco [UNESP]; Simões, Danilo [UNESP]; da Silva, Magali Ribeiro [UNESP] (Universidade Federal do Paraná, 2021)
The systematic treatment of uncertainties associated with forest production processes allows the establishment of technical and managerial strategies to mitigate the risk inherent in the application of capital demanded in the production of cuttings. Therefore, the aim of this research was to ascertain the unit risk to produce Eucalyptus cuttings using the Monte Carlo simulation method. Based on the estimate of the production cost of Eucalyptus cuttings and in the expected revenues of six productive systems, characterized as forestry investment projects, it was possible to construct cash flows followed by the metrics used for the decision of mutually exclusive investment projects. The incorporation of risk analysis had as propositions the uncertainties associated with the productive factors, in which probability distributions were attributed. Then, pseudorandom numbers were generated by the Monte Carlo simulation method, with the purpose of measuring the stochastic economic values and the probabilities of occurrences for the project metrics. The stochastic results showed that the probability of economic viability for the analyzed conditions is null. The most critical stochastic variables of forestry projects are investments and the cycle production of cuttings.
Keywords: custo de produção; Monte Carlo; net present value; nursery; production costs; Risco; Risk; valor presente líquido; viveiro